The application of phytoremediation Lemna perpusilla to increase the production performance of Nile tilapia Oreochromis niloticus in a recirculation system - Rina Hesti Utami; Kukuh Nirmala; Iman Rusmana; Daniel Djokosetiyanto; Yuni Puji Hastuti (Jurnal Akuakultur Indonesia)
ABSTRACT